2006
DOI: 10.1128/jb.00552-06
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Dimensional Structure of the Flagellar Rotor from a Clockwise-Locked Mutant of Salmonella enterica Serovar Typhimurium

Abstract: Three-dimensional reconstructions from electron cryomicrographs of the rotor of the flagellar motor reveal that the symmetry of individual M rings varies from 24-fold to 26-fold while that of the C rings, containing the two motor/switch proteins FliM and FliN, varies from 32-fold to 36-fold, with no apparent correlation between the symmetries of the two rings. Results from other studies provided evidence that, in addition to the transmembrane protein FliF, at least some part of the third motor/switch protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
292
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(319 citation statements)
references
References 53 publications
24
292
3
Order By: Relevance
“…3a). The flagellum assembly protein FliI (22,45) and the motor protein FliM (63) were present at similar levels in the wild type and SC-E1, while the level of MotB, which is part of the flagellar stator (33), was slightly reduced in SC-E1 compared to the wild type. Taken together, the Western blot analyses indicated that insertion of kan into flgE did not appreciably alter the amounts of proteins encoded by other select motility genes that were located either upstream or downstream of the mutation.…”
Section: Isolation Of the Sc-e1 Mutantmentioning
confidence: 88%
“…3a). The flagellum assembly protein FliI (22,45) and the motor protein FliM (63) were present at similar levels in the wild type and SC-E1, while the level of MotB, which is part of the flagellar stator (33), was slightly reduced in SC-E1 compared to the wild type. Taken together, the Western blot analyses indicated that insertion of kan into flgE did not appreciably alter the amounts of proteins encoded by other select motility genes that were located either upstream or downstream of the mutation.…”
Section: Isolation Of the Sc-e1 Mutantmentioning
confidence: 88%
“…Previous cryo-EM studies of basal bodies in Salmonella of the CW fliG mutation studied here have shown that the C-ring has an average 34-fold symmetry (9). The average intensity obtained from fitting a Gaussian curve to the mutant CW motor intensity distribution was normalized such that the FliM molecules corresponded to 34, yielding the average fluorescence intensity of a single FliM-YFP molecule, I mol , in our setup.…”
Section: Resultsmentioning
confidence: 99%
“…The motor is about is about 45 nm in diameter and is composed of at least 13 different proteins, all in different copy numbers. It is powered by a transmembrane ion flux (1,3,4) and consists of a core rotating against a ring of stator proteins (1,(5)(6)(7). The C ring, also called the "switch complex," is part of the rotor and localized to the cytoplasmic motor region.…”
mentioning
confidence: 99%